The relationship between size of dividend and earning changes of firm in Malaysia / Noor Fadhilah Bagia - Bagia, Nur Fadhilah (Faculty of Business and Management, 2014)
This study examines the relationship between size of dividend changes and future earnings of firm in Malaysia. My analysis using 5 companies listed in Bursa Malaysia during 2005 until 2014 period reveals a significant and positive relationship between earning changes and current dividend changes. However, there is a weakly relationship between these two variables based on research in previous year. There is hardly to determine any evidence relating dividend changes to future earning of firm. Some studies had found that dividend changes are strongly related with contemporaneous earnings changes, weakly related with one year ahead of earnings changes and largely unrelated with earnings changes beyond one year. Based on the variables, the study aim is to explore the effect between dividend changes towards earning per share. Therefore, it highlights the importance of size of dividend to ensure the improvement in company’s market value and profitability. Thus, the result of this research paper will help the manager of company especially the investors to make a decision making based on the size of dividend changes.